(untitled) (Research, Society and Development, 2020)
The Density content of the subject is taught in the 9th grade of Elementary School to introduce young students to the chemistry discipline, presenting the main properties present in all subjects, such as mass and volume. By referring to relatively new content for students, the investigative methodology can be a way to engage them in the learning process. The present article had as objective to analyze the process of construction of knowledge related to the concept of density of matter, in addition to reflecting on procedural learning enhanced by a class based on research teaching. Because it’s a student-centered approach, the methodology of research teaching makes the educational process more participatory and dialogic, providing students with the construction of scientific knowledge. Of qualitative nature, this proposal was developed from an activity applied in a class of elementary education II, in the city of Londrina, PR. It was proposed to the students the development and the dissemination of the content explored through descriptive reports of the activity. The results show that the investigative activity favored the learning of the concepts of the density of matter, in addition to presenting evidence of procedural learning during the educational process, which allows us to recommend this teaching methodology to the development of the protagonism of the student in the construction of his knowledge.